A change of scale formula for Wiener integrals of cylinder functions on abstract Wiener space - Young Sik Kim (International Journal of Mathematics and Mathematical Sciences, 1998)
The purpose of this paper is to establish the existence of analytic Wiener and Feynman integrals for a class of certain cylinder functions which is of the form: F(x)=f((h1,x)∼,⋯,(hn,x)∼),    x∈B,